1992
DOI: 10.1007/bf00154382
|View full text |Cite
|
Sign up to set email alerts
|

The photopic hill: A new phenomenon of the light adapted electroretinogram

Abstract: Utilizing a high intensity photographic flash unit, electroretinograms were recorded from normal adults under fully light adapted conditions over a 5 log unit range of stimulus luminance (-1.35 to 3.34 log cd-s/m2). At lower luminance levels b-wave amplitude increased with increased luminance until it reached a maximum (Vmax of the Naka-Ruston equation) in agreement with previous work. At higher luminance levels, the b-wave amplitude decreased to 33% of Vmax and then plateaued. This previously unreported pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
47
0
4

Year Published

1993
1993
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 8 publications
11
47
0
4
Order By: Relevance
“…In this study, the data indicated that a reduction in bwave and PT PhNR amplitude was apparent in most participants when the stimulus intensity reached 2.11 log phot tds (equivalent to 0.53 log cd.s.m -2 ). This is comparable to the stimulus intensity reported in the literature as corresponding to Vmax for the photopic b-wave luminance response function (from around 0.5 log cd.s.m -2 [40] to 0.86 log cd.s.m -2 [27]) However, the fact that the reduction in amplitude at the highest stimulus intensity was more marked for the PT PhNR data than the b-wave data, and the apparent reduction in BT PhNR amplitude in 10 individuals at the highest stimulus intensity, both suggest that this effect is not solely attributable to the well-recognised 'photopic hill' of the b-wave. responses at low stimulus intensities, but the intensity-response functions converged for all colours at the highest intensities [11,12].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In this study, the data indicated that a reduction in bwave and PT PhNR amplitude was apparent in most participants when the stimulus intensity reached 2.11 log phot tds (equivalent to 0.53 log cd.s.m -2 ). This is comparable to the stimulus intensity reported in the literature as corresponding to Vmax for the photopic b-wave luminance response function (from around 0.5 log cd.s.m -2 [40] to 0.86 log cd.s.m -2 [27]) However, the fact that the reduction in amplitude at the highest stimulus intensity was more marked for the PT PhNR data than the b-wave data, and the apparent reduction in BT PhNR amplitude in 10 individuals at the highest stimulus intensity, both suggest that this effect is not solely attributable to the well-recognised 'photopic hill' of the b-wave. responses at low stimulus intensities, but the intensity-response functions converged for all colours at the highest intensities [11,12].…”
Section: Discussionsupporting
confidence: 88%
“…Other studies have demonstrated that the photopic b-wave intensity-response data are well characterised by the Naka Rushton function at low to moderate stimulus intensities (up to around 0.8 log cd.s.m -2 ) [36,27], a finding which we have replicated in the b-wave and report for the first time in the PhNR.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The relative changes in a-and b-wave amplitude with increasing stimulus intensity resemble those described under photopic conditions as the 'photopic hill'. 18,19 This phenomenon thus appears to be a property of cones rather than be related to the adaptive state of the retina. Perlman et al suggested that the 'negative' ERG could indicate that signal transmission in the inner retina was affected, it is likely that their data merely reflect the 'photopic hill' phenomenon in a dark-adapted functionally coneisolated retina.…”
Section: Discussionmentioning
confidence: 98%